Recruitment of pregnant women to randomised trials of COVID 19 treatments, and pharmaceutical treatments received outside such trials: A research article. (August 2022) - Green, Oleia; Young, Eloise M; Oberman, Jemma; Stewart, Joel; King, Yasmin; O'Donoghue, Keelin; Walker, Kate F; Thornton, Jim G
Abstract: Objectives: To document how many pregnant women with COVID-19 reported in the literature had participated in randomised trials, what treatments they received outside such trials and compare the latter with evidence-based treatment recommendations. Study design: A systematic review of observational studies. Methods: Two clinical trial registries were searched to identify COVID-19 trials open to pregnant women. Studies were then extracted from a regularly updated list of scientific case reports and case series of confirmed or suspected maternal COVID‐19 in pregnancy to identify the number of women enrolled into a trial and the pharmaceutical treatments they received outside such trials. Results: 156 studies (case reports, case series and registries) reporting 43, 185 pregnant women with COVID-19, after de-duplication. Of these 2, 671 (6.2%) were potentially eligible for a randomised trial but only seven women (0.26%) were reported to have enrolled. For 2, 839 women the papers included information on treatment received, 1515/2829 (54%) women had received ≥ 1 treatment and in total a COVID-19 pharmaceutical treatment was administered 1, 296 times outside of a trial. In 566 (44%) cases the treatments administered to the pregnant women were not recommended by the National Institutes of Health (NIH) at the time of administration. Of 179 case reports of women with COVID 19 in pregnancy, 109/179 women received ≥ 1 COVID-19 pharmaceutical treatment and in total COVID-19 experimental pharmaceutical treatments were administered 274 times. Conclusion: During the early phase of the COVID-19 pandemic, pregnant women excluded from randomised trials did not avoid unproven or ineffective treatments.